Occurrence and risk factors of Coxiella burnetii in domestic ruminants in Lebanon. (June 2019) - Dabaja, M.F.; Greco, G.; Villari, S.; Vesco, G.; Bayan, A.; Bazzal, B. El; Ibrahim, E.; Gargano, V.; Sciacca, C.; Lelli, R.; Ezzedine, M.; Mortada, H.; et al.
Abstract: Coxiella burnetii causes diseases in humans (Q fever) and animals, domestic ruminants playing a major role in the epidemiology of the infection. Information on C. burnetii infection in Lebanon is scanty. In order to assess the prevalence of C. burnetii infection in ruminants, a cross-sectional study was undertaken in 2014. A total of 1633 sera from ruminants (865 cattle, 384 sheep and 384 goats) from 429 farms (173 cattle, 128 sheep and 128 goats), in seven provinces of Lebanon were randomly selected and assayed for the presence of antibodies. 39.86% of farms (95% CI: 35.23–44.56) resulted positive. The seroprevalence was 30.63% in Cattle-farms, 46.88% in sheep-farms and 45.31% in goat-farms. Milk samples collected from 282 seropositive animals (86 cows, 93 sheep and 103 goats) from 171 positive farms were tested by a high sensitive Real-Time PCR targeted to the IS1111 transposon of C. burnetii . The overall prevalence in farms was estimated to be 14.04%. Cattle-, sheep- and goat farm prevalence rates were 15.09%, 10% and 17.24%, respectively. The findings of the study show that C. burnetii prevalence in Lebanese domestic ruminants is related to animal species and farming practices. Indeed, the mixed herds with sheep (p < 0.01), the presence of common lambing/kidding areas (p < 0.001) in farms where the use of disinfectants was not a routine practice (p < 0.05) were identified as important risk factors. The results of the study provide baseline information for setting up herd management and public health measures for the prevention and control of Q fever in Lebanon.